Pengolahan Minyak Jelantah dan Sumber Daya Serai menjadi Lilin Aromaterapi di Kube Desa Gunung Kijang (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The community service program that has been carried out is entitled “Processing Used Cooking Oil and Lemongrass Resources into Aromatherapy Candles in KUBE, Gunung Kijang Village.” This activity involved members of KUBE (Kelompok Usaha Bersama/Joint Business Group) located in RT 009, Gunung Kijang Village, Gunung Kijang District, Bintan Regency, and was conducted on February 7, 2026. This activity was motivated by the high amount of used cooking oil waste generated by KUBE, particularly from sweet potato processing, as well as the abundance of lemongrass plants that have not been optimally utilized. The objective of this program was to reduce the risk of environmental pollution while maximizing the utilization of local village resources in the form of lemongrass. The methods used in this activity included socialization, demonstrations, and direct practice. The results of the activity showed an increase in participants’ knowledge and skills, as indicated by the questionnaire results administered before and after the activity. Aromatherapy candle products were successfully produced and are expected to help reduce waste while also becoming useful products and potential business ideas for the communit.